ANALISIS KESIAPAN UNIT USAHA SYARIAH DALAM MENGHADAPI KEBIJAKAN SPIN-OFF DI INDONESIA - Fathi Rasyid; Achmad Zaky (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to analyze the readiness of syariah business units in dealing with spin- off policies which has been regulated by the government through regulation no. 21 year 2008 and regulations of Bank Indonesia no. 11/10/PBI/2009. The analysis is conducted using performance measurement instruments containing two aspects which are financial performances and operational performance. The financial performances include capital, asset quality, earning, and liquidity; while the operational performance is the performance of banking networks. The results show that the readiness of syariah businesses is quite diverse. PT BPD Kalimantan Timur and PT Bank Tabungan Negara has the highest readiness to conduct spin-off prior to 2023 in terms of the aspect of financial and operational performances. This research can be used as a consideration by the banking regulator in Indonesia namely OJK in doing an assessment of the readiness of sharia business units that will implement a spin-off policy.Keywords: Spin-off, Readiness, Performance Measurement, Syariah Business Unit